Effect of the melt compressibility and the pressure drop rate on the cell-nucleation behavior in foam injection molding with mold opening. (July 2017) - Shaayegan, Vahid; Wang, Chongda; Costa, Franco; Han, Sejin; Park, Chul B.
Graphical abstract: Highlights: Mold opening is used to manufacture low density plastic foams. Melt compressibility plays a critical role in the dp/dt of the mold cavity. Melt packing is used to dissolve nucleated cells, reducing the melt compressibility. Proper packing pressure and duration are required to induce rapid pressure drop. Abstract: We investigated the cell-nucleation mechanisms in high-pressure foam injection molding for high expansion using the mold-opening technology. A polystyrene/carbon dioxide was used as the foam system. The cellular structure's entire formation process was monitored using an in-situ mold visualization technique. Although mold opening was used to increase the void fraction, the cell density was also significantly increased by inducing a rapid pressure drop with proper setting of the processing parameters. As in the case of high-pressure foam injection molding without mold opening, we applied a melt-packing pressure to remove the earlier nucleated cells before mold opening. Consequently, a high pressure drop rate was obtained through the decreased melt compressibility. This dramatically increased the cell density and enhanced the structural uniformity within the foamed samples. We investigated the effect of the melt-packing pressure, as well as the dwelling time of the melt/gas mixture. The packing time required to remove the cells had increased as the packing pressure had decreased. However, too lengthy a dwelling time activated another cell nucleation step through melt shrinkage before mold opening, and it deteriorated the final cell structure.